Differences of medically unexplained symptoms among patients of different ages and sexes in the psychological clinic of a general hospital and the influencing factors of MUS: A cross-sectional study - Zhang, Jie; Pan, Yu; Hong, Jiangyue; Guo, Hong; Wang, Mengyu; Liu, Xiaolei; Dong, Yanbin; Wang, Dejun; Liu, Lu; Tan, Shuping; Jiang, Ronghuan (Frontiers in Psychiatry, 2022)
Objective To analyse differences in sex, age, depression, insomnia, psychological stress, resilience, and perceived social support among patients with medically unexplained symptoms (MUS) in a psychological clinic of a general hospital, and to explore the influencing factors of MUS. Methods This is a cross-sectional study. Seven hundred forty-six first-time patients were assessed with the integrated psychosomatic comprehensive evaluation system (IPS) to evaluate their MUS, depression, insomnia, psychological stress, resilience, and perceived social support. The psychological characteristics were compared with regard to sex and age group (<25 years, low age group; 26–44 years, middle age group; >45 years, high age group). The relationships between age and MUS were explored, and how psychological stress affects MUS was analyzed using the mediator effect model. Results Different age groups had significant differences in sex, MUS, depression, psychological stress, resilience, and perceived social support. In further pairwise comparison, no significant difference existed in depression, psychological stress, resilience and perceived social support in the middle and low age groups, depression and psychological stress were higher than those in the high age group, resilience and perceived social support were lower than those of the high age group. MUS were higher in the middle age group than in the low age group. No significant difference existed between the two groups and the high age group. Age, severity of MUS, and perceived social support were significantly different between the sexes. Differences in MUS between men and women in different age groups were analyzed using two-factor analysis of variance. It revealed no interaction between sex and different age groups on MUS. The main effect analysis showed that the effects of different age groups on MUS were statistically significant. Based on pairwise comparative analysis, the MUS score in the low age group was lower than that in the middle age group. To clarify a nonlinear relationship between age and MUS, threshold effect analysis was conducted. The results indicated that the piecewise linear regression model could better depict the relationship between age and MUS. The inflection point was at the age of 60 years. Before the age of 60 years, MUS increased with age. No significant correlation existed between age and MUS after the age of 60 years. To understand the influencing factors of MUS, the intermediary effect model was analyzed using MUS as the dependent variable, psychological stress as the independent variable, resilience as mediator variable M1, perceived social support as mediator variable M2, and depression as mediator variable M3. Resilience, perceived social support, and depression had significant mediator effects on the effects of psychological stress on MUS with a total indirect effect of 69.81%. Conclusion The middle age group had greater MUS than the low age group. Before the age of 60 years, MUS increased with increasing age. Women had more severe MUS than men. Resilience, perceived social support, and depression had significant mediating effects on the effects of perceived stress on MUS. These findings suggest that clinicians should make more comprehensive and detailed evaluations and timely intervention for middle-aged and female patients. Improving psychological resilience and social support can reduce the impact of psychological stress on MUS. Therefore, psychotherapy and multidisciplinary comprehensive treatment are very important for patients is very important for patients.